Synthesising research findings - methodological guidelines for conducting the critical interpretive synthesis method - Višić, Marko (Teorija in praksa, 2024)
. Critical interpretive synthesis (CIS) integrates prior research into a theoretical framework to generate new hypotheses, theories, models and typologies. It encompasses both quantitative and qualitative data across various disciplines using a critical, reflexive, recursive and dynamic review approach. CIS favours lines of argument for synthesis and acknowledges authorial voices. Nonetheless, it faces criticism for lacking transparency and systematicity. To address these issues, we propose guidelines to enhance transparency and systematicity throughout the process. The article holds implications for research methodology.
Keywords: argumentacija; authoraial voice; authorial voice; avtorski glas; critical interpretive synthesis; Informacije; kritična interpretativna sinteza; lines of argument; Metodologija; raziskovalne metode; Raziskovanje; research methods; sintetični argument; Sinteza (filozofija); sistematičnost; synthetic argument; systematicity; transparency; transparentnost